Integrating the Electronic Health Record Into Patient Encounters: An Introductory Standardized Patient Exercise for Preclinical Medical Students - Joseph A. Cristiano; Jennifer M. Jackson; E Shen; Donna M. Williams; Leslie R. Ellis (Association of American Medical Colleges, 2022)
Introduction Increasingly, use of the electronic health record (EHR) is interwoven into even the most basic patient care tasks. Accordingly, learning how to utilize the EHR during patient encounters is important for medical students as they develop their clinical skills. Existing EHR curricula have focused primarily on doctor-patient relationship skills. We developed a session for our preclinical students on EHR-related doctor-patient relationship skills as well as on using the EHR to verify data and focus one's history taking. Methods We developed student notes, three training videos, four standardized patient (SP) cases, and a simplified, simulated EHR based on these cases. Students reviewed the notes and videos prior to class. During class, students practiced EHR-related communication and data-collection strategies by interviewing an SP while interacting with the simulated EHR. Following each encounter, students received feedback from a small group of peers and faculty. Results Two-hundred eighty-nine second-year medical students participated this session in 2019 and 2020, and 27 (19%, 2019) and 40 (28%, 2020) students, respectively, completed the postsession evaluation. Most respondents rated the SP activity as extremely or quite effective for practicing doctor-patient relationship strategies while interacting with the EHR (89%, 2019; 83%, 2020) and for practicing verification of EHR data during a patient encounter (81%, 2019; 86%, 2020). Discussion This training session was effective for introducing preclinical medical students to fundamental concepts and skills related to incorporating the EHR into patient encounters and offers a low-cost approach to teaching early medical students these important skills.